Gynecomastia Surgery: Liposuction Alone versus Liposuction with Endoscope-Assisted Glandular Excision—A Comparative Study - Sheikh Sarfraz Ali; Imran Ahmed; Mohammed Fahud Khurram; Noha Rehman; Rupraj Abhishek (Indian Journal of Plastic Surgery)
Background Gynecomastia, affecting around 30% of young males, has seen evolving surgical treatments, transitioning from traditional excision methods to contemporary techniques like liposuction. Emotional distress persists when glandular tissue is inadequately addressed, prompting exploration of combined liposuction and glandular excision procedures.